Reliability and Validation of the Child Eating Behavior Questionnaire in 3- to 6-Year-Old Spanish Children - Jimeno-Martínez, Andrea; Maneschy, Ivie; Moreno, Luis A.; Bueno-Lozano, Gloria; De Miguel-Etayo, Pilar; Flores-Rojas, Katherine; Jurado-Castro, Jose Manuel; de Lamas, Carmela; Vázquez-Cobela, Rocio; Martinez-Lacruz, Raúl; Portoles, Olga; Martínez, J. Alfredo; et al. (Frontiers in Psychology, 2022)
Introduction Eating behavior is often established during the first years of life. Therefore, it is important to make a research on it to understand the relationships that children have with food and how this can contribute to prevent the development of childhood obesity. An appropriate assessment of eating behavior can be achieved using the “Child Eating Behavior Questionnaire” (CEBQ). This questionnaire has been validated in several populations and languages, but it has never been translated, adapted, and validated for Spanish children. Aim To evaluate the reliability and internal consistency of the CEBQ questionnaire, culturally adapted and translated into Spanish (Spain), in Spanish families with children aged 3 to 6 years, as well as its association with children’s body mass index (BMI) to test its construct validity. Materials and Methods Children between 3 and 6 years old were recruited from the ongoing MELI-POP randomized controlled clinical trial, as well as from public schools located in middle class neighborhoods of Zaragoza, Spain, to complete the sample. Sociodemographic characteristics and anthropometric measures were obtained according to standardized methods. The 35-item CEBQ questionnaire was completed twice with a time difference of 3 weeks between each response. Statistical analyses included the evaluation of internal consistency and reliability of the questionnaire, a confirmatory factor analysis, and the association between the different CEBQ scales and the children’s BMI. Results A total of 197 children completed variables; 97 of them were boys (49.2%) and 100 girls (50.8%). Mean age of the total sample was 4.7 ± 0.9 years. There was a high test-re-test reliability of the questionnaire with values close to 1, with an average of 0.66 and a good internal consistency (Cronbach alpha with values above 0.7), so that a high reliability is established between the items in each scale. A gradual positive association was found between the score of different “pro-intake” scales of the CEBQ: “Food Responsiveness,” “Emotional Overeating,” and “Enjoyment of food” and the children’s BMI; at the opposite, negative associations were observed between BMI and the score of anti-intake scales “Satiety Responsiveness,” “Slowness in Eating,” and “Emotional Undereating.” Conclusion The Spanish version of the CEBQ is a useful tool to assess the eating behavior of Spanish children because the high reliability and internal validity. There is a significant association between eating behavior and BMI in Spanish children.